Improving Gas to Liquid production by Associated Gases - Ebrahimi, Hadi; Zamaniyan, Akbar; Forsat, Khaled (Journal of Petroleum Research and Studies, 2017)
Gas-to-Liquids (GTL) is a process for converting natural gas into synthetic oil, which can be further processed into fuels and other hydrocarbon-based products. The total GTL plant is self-sufficient. Therefore most of the required utilities provided, too. High energy cost is the main driving force behind currently increasing interest in the Fischer-Tropsch synthesis (FTS) for the conversion of GTL. The catalytic synthesis of hydrocarbons from CO and H2 Syngas mixtures leads to a large variety of products such as paraffins, olefins, alcohols, and aldehydes. The process uses mainly natural gas. However, other gases fuels could also be employed. Three-fourths of Iraq's natural gas resources are associated with oil. Meanwhile, Majnoon oil production is generating significant amounts of associated gas that was usually flared while different options to abate flaring are under review. The current article presents using a 10 MM m3 annually associated gases in the southern part of Iraq in 3000 BPD GTL plant. The simulation of the plant shows that the added associated gas which is currently flared could increase the productivity and there is no need to send it to the flares. Research Institute of Petroleum Industry has a license of the GTL process, both fixed-bed and slurry types.